2022
DOI: 10.48550/arxiv.2203.11223
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Star Formation in the Central Molecular Zone of the Milky Way

Abstract: The Central Molecular Zone (CMZ) is a ring-like accumulation of molecular gas in the innermost few hundred parsecs of the Milky Way, generated by the inward transport of matter driven by the Galactic bar. The CMZ is the most extreme star-forming environment in the Galaxy. The unique combination of large-scale dynamics and extreme interstellar medium conditions, characterised by high densities, temperatures, pressures, turbulent motions, and strong magnetic fields, make the CMZ an ideal region for testing curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 122 publications
4
37
0
Order By: Relevance
“…Weiß et al (2001) provided a multi-transition analysis of the molecular gas and showed the regions of most violent star formation are confined to the molecular lobes, and are arranged in a toroidal topology around the nucleus. Star-forming rings are also observed in the nearby starburst NGC 253 (Arnaboldi et al 1995;Leroy et al 2018), other local galaxies (see Buta & Crocker 1993;Böker et al 2008;Comerón et al 2010;Leroy et al 2021), and the Milky Way galaxy (see Henshaw et al 2022).…”
Section: Introductionmentioning
confidence: 87%
“…Weiß et al (2001) provided a multi-transition analysis of the molecular gas and showed the regions of most violent star formation are confined to the molecular lobes, and are arranged in a toroidal topology around the nucleus. Star-forming rings are also observed in the nearby starburst NGC 253 (Arnaboldi et al 1995;Leroy et al 2018), other local galaxies (see Buta & Crocker 1993;Böker et al 2008;Comerón et al 2010;Leroy et al 2021), and the Milky Way galaxy (see Henshaw et al 2022).…”
Section: Introductionmentioning
confidence: 87%
“…Hatchfield et al (2021) find that simulated CMZ clouds have peaks in their average density at the point where they collide violently with inflowing material. However, it is unlikely that the collision observed in cloud 'd' is is driven by bar inflow, as cloud 'd' is not located near any proposed entry point to the CMZ (Henshaw et al 2022a). It is also extremely unlikely that cloud 'd' is a collision occurring downstream from an entry point, as the collision is currently ongoing.…”
Section: Source Of Converging Flowsmentioning
confidence: 99%
“…Bressert et al 2012;Ginsburg et al 2012;Urquhart et al 2013;Longmore et al 2013aLongmore et al , 2017, such clouds have remained elusive in the Milky Way. The most promising examples to date have generally been found in the 'Central Molecular Zone' (CMZ) -the inner few hundred pc of the Galaxy (Henshaw et al 2022a) (the Henshaw+22 reference has been added in this edit). In particular, a region of the CMZ known as the 'dust ridge' (Lis et al 1994), contains a collection of six massive (10 5 M ), compact (radius ∼1-3 pc), and largely quiescent clouds (excluding the Sagittarius B2 complex, one of the most active sites of high-mass star formation in the entire Milky Way, e.g.…”
mentioning
confidence: 99%
“…2 We normalize the IMF so that 0.15 so that m ∼ 0.5), and a Ṁ * ∼ 0.1 (e.g. Henshaw et al 2022 and references therein) we obtain Ėkin,winds ∼ 10 40 erg/s for the entire volume of the CMZ to which the star formation estimate refers. Converting this to a per-volume estimate is not trivial.…”
Section: Energy Deposition By Stellar Winds In the Cmzmentioning
confidence: 99%
“…Converting this to a per-volume estimate is not trivial. First, the star formation is not uniformly distributed over the CMZ volume, as is clear from Henshaw et al (2022), who compare different estimates of Ṁ * in the CMZ using different tracers and studying different volumes: as can be seen in their Table 1, there is no strong correlation between the volume of the CMZ studied and the derived value of Ṁ * , which is to be expected if the star formation, massive stars, and molecular clouds are all spatially correlated and only cover a small fraction of the CMZ volume. If we assume that most of this star formation takes place in the same region of the central CMZ covered by the clouds studied in Kauffmann et al (2017a) (radius of ∼ 100 pc, height of ∼ ±5 pc from the Galactic plane), then we obtain Ėkin,winds ∼ 4 × 10 34 erg s −1 pc −3 (corresponding to a population of about 1500 O and B stars of all evolutionary stages within the CMZ).…”
Section: Energy Deposition By Stellar Winds In the Cmzmentioning
confidence: 99%